C3d adjuvant activity is reduced by altering residues involved in the electronegative binding of C3d to CR2 - Toapanta, Franklin R (2010)
The final degradation product of the complement protein C3, C3d, has been used as a molecular adjuvant to various antigens. Chimera proteins of the antigen and multiple copies of C3d were developed to test the adjuvant effect of this molecule. The main mechanism by which C3d enhances the immune response is interaction with CR2. In-vitro studies showed that the avidity of C3d for CR2 is affected by residues located at the interacting surface (e.g. 170N) as well as by residues located in other areas. The role of the latter residues has been proposed to depend on the electrostatic nature of the C3d-CR2 interaction, where the charges of the whole molecules are responsible for their binding. C3d is primarily a negatively charged molecule, while CR2 is a positive one. Previous experiments demonstrated that elimination of a positive charge (K162A) in C3d enhanced its avidity for CR2, while elimination of negative charges or addition positives ones (D163A N170R, respectively), impaired the avidity for CR2. Despite the extensive in-vitro research, the role of these residues in the adjuvant effect of C3d is unclear. To study the role of residues at the interacting and non-interacting surface of C3d on the adjuvanticity, single as well as a double residue substitutions were engineered in the murine C3d (R162A, D163A, N170R and D163A-N170R) gene. Two copies of these mutant molecules were fused to HIV-1 Env(gp120) and the proteins were tested for their avidity to bind CR2 (sCR2). Later, these DNA constructs were tested in mice to determine their adjuvant capability. Mutation at residue 162 (R162A) neither enhanced nor impaired the avidity of Env(gp120)-C3d(2) for sCR2 in-vitro. Mutations at residues D163A and N170R, on the other hand, reduced the binding affinity of Env(gp120)- C3d(2) for sCR2. Furthermore, these mutations synergized and abolished the interaction of C3d for CR2. The data correlated with the adjuvant capability of these molecules in the mouse model. In summary, residues that alter the electronegative status of C3d (D163A and N170R) impair the binding of chimera proteins to CR2, reducing the adjuvant activity of this molecule.